Gambaran Keterlibatan Ayah dalam Pengasuhan Anak Usia Dini: Baseline dari Rancangan Program Intervensi untuk Ayah - Hayuning Zaskya Nugrahani; Rose Mini Agoes Salim; Airin Yustikarini Saleh (Fakultas Psikologi Universitas Tarumanagara, 2021)
Previous studies have shown that father plays an important role in children’s lives (Lamb, 2010). Father involvement has been found to promote independence, self control, and socialize gender role in early childhood children. This study aimed to obtain baseline data as the first stage of preparation of intervention program of father involvement as an intervention for father who had early childhood children. 54 fathers who had early children aged between 1 to 5 year olds were involved in this study. The design in this study was non-experimental research, one-shot study. The instrument was developed based on five aspects of father involvement (Pleck, 2010). The results of this study showed that father involvement in parenting for early childhood was moderate (M = 3.14). The control aspect of the father involvement reached the highest score (M = 3.31), while the lowest aspects of father involvement were in the aspect of positive involvement activities (M = 3.04) and process responsibility (M = 3.04). Based on this study, further research was necessary to develop a psychoeducation intervention program that optimalized father involvement in parenting for early childhood.